Tuesday
March 28, 2017

Post a New Question

Posted by on .

I need help to solve this problem by factoring: 2x^2-x-3=0

  • Algebra - ,

    (2x-3)(x+1)

  • Algebra - ,

    2x^2-x-3=0
    first step: 2*2x^-x-3=0
    4x^-x-3=0
    (4x^-4x)+(3x-3)=0
    4x(x-1)+3(x-1)
    (4x+3)(x-1)=0
    (4x+3)=0 (x-1)=0
    4x+3=0 X-1=0
    -3 -3 -1 -1
    4x=-3 x=-1
    x=-3/4
    Therefore, X=(-3/4, -1)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question